ACTIVITY OF PROPYL p-BENZOYLOXYBENZOATE AS A GLUTATHIONE S-TRANSFERASE(S) INHIBITOR: THE COMPARISON BETWEEN COMPUTATIONAL CHEMISTRY APPROACH AND EMPIRICAL OBSERVATION - Enade Perdana Istyastono; Agnes Nora Iska Harnita; Sudibyo Martono (Universitas Gadjah Mada, 2006)
The activity of propyl p-benzoyloxybenzoate as a glutathione S-transferase(s) (GSTs) inhibitor has been examined through computational chemistry based theoretical approach and laboratory experiment. This research was related to the nature of GSTs as multifunctional enzymes, which play an important role in the detoxification of electrophilic compounds, the process of inflammation and the effectivities of anticancer compounds. Quantitative Structure-Activity Relationship (QSAR) study, which was established on curcumin and its derivatives using computational chemistry approach, was used to examine the theoretical activity of p-benzoyloxybenzoate as a GSTs inhibitor. Empirical observation on GSTs inhibition was examined using formation reaction model of GS-CNB conjugate through conjugation of 1-chloro-2,4-dinitrobenzene (CDNB) and glutathione (GSH) with GSTs (prepared from rat's liver) as catalysts. The result showed that the difference between the activities of propyl p-benzoyloxybenzoate as a GSTs inhibitor obtained from the computational chemistry approach and the empirical observation were not statistically significant at 95% level of confidence.